Desenvolvimento de habilidades visuais gráficas: a aprendizagem da engenharia industrial mecânica através da prática do desenho - Alves, Catarina Maria Damasceno (2017)
The deficiency of the graphic visual ability prevails in the formation of the student of the course of Engineering, while the ability to see and graphically represent the shape of constructed objects is not developed in the imaginary, youngsters and adults tend to maintain the same characteristics of children's design. Therefore, in basic education, the stimulus to the practice of drawing does not have the same privilege o speech and writing in curricular subjects. Consequently, these students present a resistance in the learning of the Technical Design. Some important considerations about the design are highlighted in: its position in the culture; The reason why most people stop drawing; And the role of the educator in this process. In addition, the research was based on the studies of some authors that define the design, its valuation, use and perception. This work presents a research on the relevance in the development of the graphic visual ability in the training of the students of the course of the Industrial Mechanical Engineering course of the Federal Institute of Bahia - IFBA, Salvador Campus, through a set of procedures and / or method capable to stimulate the graphic expression from the practice of the Design. For an adequate understanding about the design, it is needed to rediscovery the importance of drawing practice.